Development of Rainbow Mathematics Card in TGT Learning For Increasing Mathematics Communication Ability - Sugianto, Rahmad; Cholily, Yus Mochamad; Darmayanti, Rani; Rahmah, Kamilia; Hasanah, Niswatun (Mathematics Dept, Math. and Science Faculty, Universitas Negeri Semarang, 2022)
Mathematics communication, which includes writing, drawing, and expressing mathematics, is essential in learning mathematics. The teacher needs to design learning to develop the ability to communicate mathematically. Questions presented in the Rainbow Mathematics Card (RMC) allow participants to be educated to convey the ideas and concepts that become part of developing mathematics communication ability. The study aims to make mathematics communication ability TGT learning with RMC. A type study is a mixed method that is designed and experimented with in subjects research. Data was obtained through test mathematics ability communication before and after learning using a paired t-test. The results showed an enhanced mathematics communication ability through the TGT learning model with RMC.Komunikasi matematika yang meliputi menulis, menggambar, dan mengekspresikan matematika, sangat penting dalam pembelajaran matematika. Guru perlu merancang pembelajaran untuk mengembangkan kemampuan berkomunikasi matematis. Soal-soal yang disajikan dalam Rainbow Mathematic Card (RMC) memungkinkan peserta dididik untuk menyampaikan ide dan konsep yang menjadi bagian dari pengembangan kemampuan komunikasi matematika. Tujuan penelitian ini untuk tes peningkatan kemampuan matematis melalui pembelajaran TGT dengan RMC. Jenis studi adalah metode campuran yang kemudian dikembangkan dan dieksperimentasikan ke subjek penelitian. Data diperoleh melalui tes kemampuan komunikasi matematis sebelum dan sesudah pembelajaran menggunakan uji t berpasangan. Hasil penelitian menunjukkan peningkatan kemampuan komunikasi matematis melalui pembelajaran TGT dengan RMC.